Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Integrative transcriptomics and metabolomics reveal distinct metabolic reprogramming in luminal and triple-negative breast cancer cells - Ranawade, Preeti; Sonwane, Babasaheb; Bose, Ganesh; Jadhav, Revati; Joshi, Rakesh; Mittal, Smriti (Molecular Omics, 2026)
Breast cancer subtypes exhibit significant molecular and metabolic heterogeneity, influencing their aggressiveness and therapeutic responses. Among them, triple-negative breast cancer (TNBC) is highly aggressive and often resistant to conventional therapies. To investigate the metabolic programming of this aggressiveness, we conducted an integrated transcriptomics and metabolomics analysis comparing the MCF-7 (luminal A, ER+/PR+) and MDA-MB-231 (TNBC) breast cancer cell lines. Transcriptome analysis of MCF-7 and MDA-MB-231 revealed the differential expression of genes involved in key metabolic pathways. Metabolomics data, further corroborated by transcriptomics, suggest pathway enrichment in beta-alanine, histidine, glutathione, nucleotide metabolism, and the tricarboxylic acid cycle. MDA-MB-231 cells displayed a metabolically aggressive phenotype with enhanced oxidative phosphorylation, redox adaptation, and nucleotide turnover. In contrast, MCF-7 cells showed a more regulated amino acid and redox metabolism profile. The integration of transcriptomic and metabolite profiles highlighted potential metabolic vulnerabilities in TNBC, offering insights into subtype-specific differences at the molecular level.